Proposed emerged and enhanced routing protocols for wireless networks - Dheyaa Jasim Kadhim; Ali Abdulwahhab Mohammed (Institute of Advanced Engineering and Science, 2021)
The problem motivation of this work deals with how to control the network overhead and reduce the network latency that may cause many unwanted loops resulting from using standard routing. This work proposes three different wireless routing protocols which they are originally using some advantages for famous wireless ad-hoc routing protocols such as dynamic source routing (DSR), optimized link state routing (OLSR), destination sequenced distance vector (DSDV) and zone routing protocol (ZRP). The first proposed routing protocol is presented an enhanced destination sequenced distance vector (E-DSDV) routing protocol, while the second proposed routing protocol is designed based on using the advantages of DSDV and ZRP and we named it as DS-ZRP routing protocol. The third proposed routing protocol is designed based on using the advantaged of multipoint relays in OSLR protocol with the advantages of route cashing in DSR protocol, and we named it as OLS-DSR routing protocol. Then, some experimental tests are doing by demonstration case studies and the experimental results proved that our proposed routing protocols outperformed than current wireless routing protocols in terms of important network performance metrics such as periodical broadcast, network control overhead, bandwidth overhead, energy consumed and latency.